The user with respiratory symptoms of tuberculosis in the primary care: assessment of actions according to national recommendations - Luize Barbosa Antunes; Jéssica Oliveira Tomberg; Jenifer Harter; Lílian de Moura Lima; Dagoberta Alves Vieira Beduhn; Roxana Isabel Cardozo Gonzales (Rev Rene)
Objective: to investigate the evaluation of the user with respiratory symptoms of tuberculosis in Primary Health Care services according to the norms of the National Program for Tuberculosis Control. Methods: cross-sectional study with application of a form to 99 people with pulmonary tuberculosis. Results: a total of 87.9% participants reported cough as the symptom that motivated the search for Primary Care; from these, 27.3% sought Primary Care units, 96.3% received care in this service, of which 46.2% reported that sputum smear was requested by professionals in the units.Conclusion: more than half of participants sought secondary or tertiary services due to the symptoms of tuberculosis, and also less than half of patients assisted in Primary Care had diagnostic tests requested by professionals of that service.